Patient Information Leaflets for Lumbar Spine Surgery: A Missed Opportunity. (December 2020) - Low, Matthew; Burgess, Louise C; Wainwright, Thomas W
Background: High-quality patient information is recommended to help reduce procedure-related anxiety and encourage patients to become active participants in their recovery. The objective of this study was to analyze the quality of patient information leaflets (PILs) given to National Health Service (NHS) patients ahead of lumbar spine surgery. Methods: The DISCERN tool was used to evaluate the quality of PILs, sourced from NHS websites. Results: Thirty-two PILs on lumbar surgery were included. Two (6%) leaflets were considered poor, 13 (41%) were marked as fair, 14 (44%) were of good quality, and 3 (9%) were scored as excellent. The total mean score was 55 (30-74), which corresponds to good quality. The lowest scoring questions were sources of information (Q4), balanced/unbiased content (Q6), and explanation of no treatment (Q12). Conclusions: There is considerable variation in the quality of PILs provided ahead of lumbar spine surgery. The scope for improvement is clear, and as the move toward patient-centered, evidence-based care continues, it is important that hospital resources provide recommendations based upon evidence of clinical effectiveness.